Perception on blackflies and community ownership of the “Slash-and-Clear” vector control intervention in onchocerciasis-endemic communities along Edo-Ondo border in Southern Nigeria - Monsuru Adebayo Adeleke; John Agbonifo; Olabanji Ahmed Surakat; Bertram Nwoke; Kenneth Opara; Hayward Mafuyai; Oluwadamilare Ganiu Dauda; Dauda Ishola Azeez; Olanike Oladipupo; Happy Poko; Francisca Olamiju; Emmanuel Emukah; et al. (PLoS ONE, 2026)
Background Many communities along the Edo-Ondo border in southern Nigeria remain highly endemic for onchocerciasis. Despite more than two decades of mass drug administration (MDA), transmission persists, necessitating the National Onchocerciasis Elimination Committee (NOEC) to designate the zone as special intervention hotspots. Slash-and-Clear (S&C) has emerged as a promising, community-based approach that can be integrated with ongoing MDA campaigns. This study assessed community knowledge of blackfly, onchocerciasis and willingness to sustain S&C without external financial or logistical support. Method Structured questionnaire was administered to 79 key informants from Edo (n = 59) and Ondo (n = 20) communities along Ose River. Focus group discussions (FGDs) were conducted pre- and post-intervention (April 2023 and April 2025, respectively) with participants from 76 communities that participated in slash-and-clear. Three communities declined due to security and socio-cultural reasons. Results Prior to intervention, all 79 (100%) key informants reported frequent blackfly bites and expressed the need for strategies to reduce the nuisance. FGD findings corroborated this, with participants recognizing blackflies and their biting burden but showing limited awareness of onchocerciasis as a disease. Common protective measures included wearing long clothing and applying chemical substances on skin to prevent bites. At post-intervention, participants collectively reported noticeable decline in blackfly activity, which reinforced community enthusiasm for sustaining the intervention. Although some communities expressed willingness to continue without monetary incentives, the provision of essential tools and materials was consistently emphasized by majority. Conclusion The reduction in blackfly nuisance was a motivator for community’s willingness to sustain the intervention. Continued support and routine monitoring by the Edo and Ondo State governments, especially for communities reluctant to participate without financial incentives, are critical to prevent reinfestation in committed areas. This supervision will ensure the broader success of the S&C strategy and the elimination of onchocerciasis in communities along the Edo-Ondo border.